Handedness and schizotypy: The potential effect of changing the writing-hand. (30th August 2016) - Tsuang, Hui-Chun; Chen, Wei J.; Kuo, Shu-Yu; Hsiao, Po-Chang
Abstract: Mixed-handedness, which has been associated with schizotypy in recent studies, might exist for at least two different reasons: it is innate or it has been forced. We examined whether the association between mixed-handedness and schizotypy differs depending on its source. We enrolled 3485 college students in Taiwan. We used both the Perceptual Aberration Scale and Schizotypal Personality Questionnaire to assess schizotypy, and the Annett Hand Preference Questionnaire to assess handedness. Two ways of classifying handedness were examined: the three-way classification based on Annett's categories and mixed- vs. non-mixed-handedness based on Degree of Handedness. Both mixed-handedness groups showed higher positive schizotypy scores. Among mixed handers, those who had been required to change their writing hand from left to right had higher positive schizotypy scores. Being forced to change writing hand seemed to be related to a higher level of schizotypy. The potential effect of the social pressure against using the left hand for writing is discussed. Highlights: Mixed handers who had changed their writing hand had higher schizotypy scores. Being forced to change writing hand was related to a higher level of schizotypy. Both mixed-handedness groups showed higher positive schizotypy scores. The effect of the social pressure against using left hand for writing is discussed.